2006
DOI: 10.1111/j.1540-4560.2006.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Focus of Child Maltreatment Research and Practice Within Psychology

Abstract: Professions functionally define a field by the types of behaviors or circumstances to which they direct their attention and efforts. For psychology and mental health professionals concerned with child maltreatment, child sexual abuse has been the dominant interest over the past two decades and has been virtually synonymous with child maltreatment within psychology. This is discrepant from the broader scope of child maltreatment, as seen both in child welfare populations and in the general population. In child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 74 publications
(74 reference statements)
0
31
0
1
Order By: Relevance
“…This is especially true in cases of child neglect. As discussed earlier, neglect presents as, and has different effects than other types of maltreatment (Chaffin, 2006;Dubowitz, 2008). For cases where parental rights are being terminated due to neglect, it may be beneficial, as indicated by Erin's story, to have some social services, such as family therapy continue.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially true in cases of child neglect. As discussed earlier, neglect presents as, and has different effects than other types of maltreatment (Chaffin, 2006;Dubowitz, 2008). For cases where parental rights are being terminated due to neglect, it may be beneficial, as indicated by Erin's story, to have some social services, such as family therapy continue.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The impetus of change to prevent child maltreatment must come from the work and the public statements of persons who have been affected by child disparities that are exacerbated by living in disadvantaged neighborhoods and communities, suggesting that child neglect in particular is rooted in social factors and issues that are difficult to change (Chaffin, 2006). Children maltreated in the context of parental neglect and who additionally experience community violence, poverty, poor nutrition, social deprivation, and inadequate medical care also continue to be at-risk for continued exposure to trauma in their futures (Briere & Lanktree, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaffin (2006), Epstein (1997), andLittell (1997) examined the results of family preservation services and suggested that there is limited evidence of long-term effectiveness of addressing those issues. They each suggest the need for additional rigorous studies that evaluate the process of treatment to determine the mechanisms that lead to sustainable outcomes.…”
Section: Contraindications Specific To Hbftmentioning
confidence: 99%
“…Yet, compared to other forms of maltreatment, considerably less research attention has focused on these types of maltreatment (Chaffin, 2006). This situation is concerning given that existing research suggests psychological maltreatment and neglect are associated with equally severe or even greater short-and long-term consequences than other forms of child maltreatment (see Claussen & Crittenden, 1991;Hart, Brassard, Binggeli, & Davidson, 2002).…”
mentioning
confidence: 99%